The effect of peer bullying education on adolescents' knowledge, attitudes and behaviors towards bullying - EROL, SAİME (ELSEVIER SCIENCE BV, 2012)
The study was of quasi-experimental design. It was conducted to determine the effect of peer bullying education given to adolescents on their knowledge, attitude and behaviors. Adolescents between 12-15 years of age who are all studying at a primary school, 141 adolescent were included in training. The 26 questions were asked to adolescents that measure knowledge, attitudes and behaviour. Training lasted for 5 weeks and meeting was held with students one hour each week. Increasing in knowledge, attitude and behaviour scores of adolescents before and after education were found statistically significant. When viewed in scores of knowledge between the classes, knowledge score was statistically increased in all grades. However, in 6th grades scores were lower compared to the other classes. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylu
Keywords: peer bullying; peer bullying education; school health nursing; adolescents